2007
DOI: 10.1590/s0004-27302007000500013
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma de tireóide na infância e adolescência

Abstract: RESUMOAproximadamente 10% das neoplasias de tireóide aparecem abaixo dos 21 anos e representam 3% das neoplasias da infância, com predomínio em meninas (2F:1M). São papilíferos em 90% casos e mais freqüentemente bilaterais, multifocais e de maior dimensão. Invasão de cápsula e metástases ganglionar ou pulmonar são mais freqüentes que no adulto. O efeito carcinogênico da radiação é especialmente importante na criança pré-púbere. Em 5% dos casos de PTC existe história familial. Genes como o RET/PTC, RAS e BRAF e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
2
0
3
Order By: Relevance
“…Thyroid function tests are not helpful because children with solitary thyroid nodules are usually euthyroid (7). However, tumor markers (calcitonin or thyroglobulin) might be elevated in thyroid carcinoma and should therefore be investigated (17)(18)(19). The ultrasound of the thyroid gland provides important information to classify the underlying condition and should be the first diagnostic step (20) after a detailed physical examination of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid function tests are not helpful because children with solitary thyroid nodules are usually euthyroid (7). However, tumor markers (calcitonin or thyroglobulin) might be elevated in thyroid carcinoma and should therefore be investigated (17)(18)(19). The ultrasound of the thyroid gland provides important information to classify the underlying condition and should be the first diagnostic step (20) after a detailed physical examination of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…as questões prognósticas de morbi-mortalidade revelam os principais tipos de câncer que acometem a população pediátrica, sua prevalência, o quadro epidemiológico (sexo, idade, raça, entre outros), as taxas de cura, a estimativa de sobrevida e o quantitativo de óbitos 14 .…”
Section: Discussionunclassified
“…Monte et al showed that about 10% of neoplasms usually occur in people younger than 21 years old, which represents 3% of all childhood neoplasms. Thus, the carcinogenic effect of radiation is particularly concerning in prepubertal individuals [ 7 ]. Worldwide trends indicate that medical radiation exposure has been increasing, due to cardiological procedures, and particularly in cases involving CHD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%